Eksistensi dan Dedikasi Ulama Perempuan Terhadap Pendidikan Islam di Nusantara - Helmiannoor, Helmiannoor; Musyarapah, Musyarapah (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
The term scholars, so far more dominant is associated with men. However, the fact that many female figures have been found in Islamic history, especially in Malay families. Therefore, the disclosure of women's economic side became a noteworthy study. The focus of the problem in this study was discussing the existence and dedication of female clerics on Islamic education in Malay family. This research is a type of literature research or called a library research. Data sources include books and research outcomes related to the role and gait of female scholars in the archipelago. While the data analysis technique uses content analysis technique. The results of this study concluded that public recognition of female scholars in the archipelago is still lacking. The dedication of female scholars to Islamic education can be seen in the form of providing enlightenment to the community, organizing a regular Taklim assembly, being the leader of educational institutions as well as the oganization of other Islamic, and devote All efforts, energy, and time for the development of Islamic education in the archipelago.